2002
DOI: 10.1073/pnas.082644299
|View full text |Cite
|
Sign up to set email alerts
|

Formation of oriented molecular nanowires on mica surface

Abstract: Molecular ''nanowire'' structures composed of the charge transfer complex of a bis-tetrathiafulvalene substituted macrocycle and tetrafluorotetracyanoquinodimethane were constructed on mica substrates by employing the Langmuir-Blodgett technique. The nanowires transferred from a dilute aqueous potassium chloride subphase had typical dimensions of 2.5 nm ؋ 50 nm ؋ 1 m. The nanowires are oriented to specific directions, corresponding to the directions of the potassium-ion array on the mica surface having sixfold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 29 publications
5
64
0
Order By: Relevance
“…The similarly oriented arrangement of self-assemblies on mica has also been found in other systems, which is thought to result from the template inducement of a metal-ion array on the crystalline lattice surface of mica having sixfold symmetry [24,[30][31][32]. In our recent work, we also reported that the Langmuir-Blodgett films of a rod-coil block oligomer with a shorter PEO coil than EO 16 OPV could present the oriented rod-like domains on mica [21].…”
Section: Oriented Arrangement Of the Stripes On Micamentioning
confidence: 79%
“…The similarly oriented arrangement of self-assemblies on mica has also been found in other systems, which is thought to result from the template inducement of a metal-ion array on the crystalline lattice surface of mica having sixfold symmetry [24,[30][31][32]. In our recent work, we also reported that the Langmuir-Blodgett films of a rod-coil block oligomer with a shorter PEO coil than EO 16 OPV could present the oriented rod-like domains on mica [21].…”
Section: Oriented Arrangement Of the Stripes On Micamentioning
confidence: 79%
“…Organic conducting 1D nanostructures have been studied with the expectation for potential application owing to their low density and flexibility for molecular design compared with the inorganic nanostructures [170][171][172][173]. Despite a variety of synthetic methods to the organic 1D nanostructures, creation of template-free and facile approaches are still required for future practical application [174,175]. Naka and Chujo [176] introduced the synthesis of organic-metal hybrid nanowires via electron-transfer reaction between tetrathiafulvalene (TTF) and a gold ion.…”
Section: Organic-metal 1d Nanostructuresmentioning
confidence: 99%
“…Oriented structures of p-conjugated polymers on mica substrates have also been reported. [27][28][29][30] Akutagawa et al indicated that nanowires are oriented along the direction of the metal-ion array on a mica surface with sixfold symmetry during transformation of the film. [27] Li et al reported a rod-coil molecule containing a PEO block with seven repeating units similar to 18-crown-6, which is capable of recognizing a K + cation array on the mica surface with sixfold symmetry.…”
Section: Transferred Films On a Solid Supportmentioning
confidence: 99%
“…[27][28][29][30] Akutagawa et al indicated that nanowires are oriented along the direction of the metal-ion array on a mica surface with sixfold symmetry during transformation of the film. [27] Li et al reported a rod-coil molecule containing a PEO block with seven repeating units similar to 18-crown-6, which is capable of recognizing a K + cation array on the mica surface with sixfold symmetry. [28] In our case, the number of ethylene oxide repeating units of the Y21 molecule is three times that of the rod-coil molecule reported by Li et al, and the PEO block with 21 repeating units could also interact with K + cations according to the sixfold symmetry axes of the mica substrate.…”
Section: Transferred Films On a Solid Supportmentioning
confidence: 99%